Analisis Muatan Nilai Karakter dalam Buku Teks Pendidikan Pancasila SMP Kelas VII - Wafa Khairunisa; Dadang Sundawa (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Basically, one strategy in shaping the character of the nation's next generation is through instilling character values ​​in students at school, which can be implemented using the Pancasila Education textbook. This research aims to strengthen students' values ​​and ethics, so that they become individuals who are honest, empathetic and responsible, who in turn are expected to be pioneers of change that bring hope for a better future. This research methodology is a qualitative approach with content analysis methods. The results of the research show that the character values ​​contained in the Pancasila Education textbook are spread throughout the book's chapters, including (1) the introductory section which contains an invitation or exclamation, (2) the content of the material which includes students' activities in searching for information and reading discourse, as well as (3) a closing section which includes reflection, individual and group assessment.